Transformasi Identitas Anggota Geng Motor Studi Fenomenologi mengenai Transformasi Anggota Geng Motor XTC yang menjadi Organisasi Masyarakat Kabupaten Karawang - Tiara Nurfadilah; Reddy Anggara; Muhamad Ramdhani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Singaperbangsa Karawang, 2018)
ABSTRACTThe purpose of this research is to know how Identity of XTC motorcycle gang member before transforming and after transforming and meaning member XTC Kabupaten Karawang. The method used in this study is a qualitative research method with phenomenology studies that explain the phenomenon of human behavior experienced in consciousness and seek understanding of a person in building meaning and concepts that are intersubjective. Techniques of collecting data through interviews, observation, documentation and document review. Techniques of collecting data through interviews, observation, documentation and document review. Sources of data in this study using primary data and secondary data. Number of informants in this study there are 10 people who are members of XTC Kabupaten Karawang is active in XTC activities.Data analysis techniques used are data reduction, data presentation, conclusion and verification. Based on the results of research that the identity of XTC members before becoming a community organization is personally disobedient to the rule of law and always do not want to lose. It tends to be negative. While the identity of XTC members after becoming a community organization is obedient to the rule of law, eliminating a sense of hatred towards opponents, doing positive activities. Meaning of XTC member for XTC member Kabupaten Karawang is the meaning of family / brotherhood, soul and togetherness. Keywords: Identity Transformation, Community Organization